Lost childhoods: poverty, trauma, and violent crime in the post-welfare era - Soyer, Michaela (University of California Press, 2018)
"Lost Childhoods focuses on the life-course histories of 30 young men serving time in the Pennsylvania adult prison system for crimes they committed when they were minors. The narratives of these young men, their friends, and relatives reveal the invisible yet deep-seated connection between the childhood traumas they suffered and the violent criminal behavior they committed during adolescence. By living through domestic violence, poverty, the crack epidemic, and other circumstances, these men were forced to grow up fast, all while familial ties that should have sustained them were broken at each turn. The book goes on to connect large-scale social policy decisions and its effect on family dynamics and demonstrates the limits of punitive justice"--Provided by publisher